2012
DOI: 10.1111/j.1365-2966.2012.20855.x
|View full text |Cite
|
Sign up to set email alerts
|

Interesting dynamics at high mutual inclination in the framework of the Kozai problem with an eccentric perturber

Abstract: We study the dynamics of the 3D three‐body problem of a small body moving under the attractions of a star and a giant planet which orbits the star on a much wider and elliptic orbit. In particular, we focus on the influence of an eccentric orbit of the outer perturber on the dynamics of a small highly inclined inner body. Our analytical study of the secular perturbations relies on the classical octupole Hamiltonian expansion (third‐order theory in the ratio of the semimajor axes), as third‐order terms are need… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The curves of Tω and TΩ given in Fig. 1 are in good agreement with the ones shown in Libert & Delsate (2012) (see Fig. 8 in their work).…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…The curves of Tω and TΩ given in Fig. 1 are in good agreement with the ones shown in Libert & Delsate (2012) (see Fig. 8 in their work).…”
Section: Introductionsupporting
confidence: 86%
“…by means of Lie-series transformation method to determine the fundamental frequencies, similar to the method used in Libert & Henrard (2008). Then, Libert & Delsate (2012) showed that this region presents an equality of two fundamental frequencies (please refer to Fig. 8 in their work), and thus they concluded that the long-term stable dynamics at inclination of ∼35 • is due to the existence of the secular resonance associated with σ = ω − Ω.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations